2022
DOI: 10.1186/s12906-022-03800-0
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in silico analysis of ‘Taikong blue’ lavender essential oil in LPS-induced HaCaT cells and RAW264.7 murine macrophages

Abstract: Background ‘Taikong blue’ lavender, a space-bred cultivar of Lavandula angustifolia, is one of the main lavender essential oil production crops in Xinjiang Province, China. Several cases of local usage indicated that ‘Taikong blue’ lavender essential oil (TLEO) had excellent anti-inflammatory and antioxidant properties for skin problems. However, to date, substantial data on these functions are lacking. In this study, we aimed to investigate the composition and bioactivities of TLEO and the pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 38 publications
1
3
0
Order By: Relevance
“…These results indicate that bornyl acetate revealed the best pharmacokinetic properties compared to cubebol, and it can be considered in further experiments. Similar to our study, Wei et al, who found linalool and linalyl acetate (29.48 and 40.97%, respectively) in lavender, proved that these major LSEO components had no toxicity and were safe to be used as food or medication [ 78 ]. A recent study reported that linalyl acetate (39.7%), linalool (33.6%), and terpinen-4-ol (14.9%) were the most abundant lavender EOs and that they possessed antiviral activities against many DNA and RNA viruses [ 79 ].…”
Section: Resultssupporting
confidence: 91%
“…These results indicate that bornyl acetate revealed the best pharmacokinetic properties compared to cubebol, and it can be considered in further experiments. Similar to our study, Wei et al, who found linalool and linalyl acetate (29.48 and 40.97%, respectively) in lavender, proved that these major LSEO components had no toxicity and were safe to be used as food or medication [ 78 ]. A recent study reported that linalyl acetate (39.7%), linalool (33.6%), and terpinen-4-ol (14.9%) were the most abundant lavender EOs and that they possessed antiviral activities against many DNA and RNA viruses [ 79 ].…”
Section: Resultssupporting
confidence: 91%
“…A dexamethasone group (DEX, 1 μM) was used as a positive control. After induction with 1 μg/mL LPS for 4 h, RNA was extracted, and cDNA was prepared using real-time fluorescence quantitative PCR according to the method from Vazyme [ 88 ]. The primers were synthesized by Sangon Biotech (Shanghai) Co., Ltd. (Shanghai, China), and the sequences are shown in the Supplementary Material (Table S1) .…”
Section: Methodsmentioning
confidence: 99%
“…The HaCaT cells were cultured in DMEM supplemented with 10% FBS, 1% P/S and 1% glutamine and maintained in a humidified 5% CO 2 incubator at 37 °C. The cytotoxic activities of samples were measured by colorimetric MTT assay [ 20 ]. The cells were seeded into a 96-well plate at a density of 2 × 10 5 cells/mL.…”
Section: Methodsmentioning
confidence: 99%